Short Communication: Antioxidant and antibacterial properties of tree fern Cyathea contaminans - Ahmad Faizal; Intan Taufik; Anisah Firda Rachmani; Alda Wydia Prihartini Azar (Society for Indonesian Biodiversity, 2020)
Abstract. Faizal A, Taufik I, Rchman AF, Azar AWP. 2020. Short Communication: Antioxidant and antibacterial properties of tree fern Cyathea contaminans. Biodiversitas 21: 2201-2205. Cyathea contaminans (Wall. ex Hook) Copel is a tree fern used in traditional practices as herbal remedies to treat different kinds of diseases. To explore its further medicinal uses, we designed a study to determine the antioxidant and antibacterial activities of polar and non-polar extracts of this fern. The fern leaves (mature fronds), young fronds, and hairs were collected from Tangkuban Perahu Nature Park, West Java, Indonesia, and were extracted by methanol 80% or n-hexane. Antioxidant activity was evaluated by DPPH (1,1-diphenyl-2-picrylhydrazyl) assay, whereas antibacterial activity was measured by growth inhibition of Escherichia coli and Staphylococcus aureus. Results showed that methanol extract from mature leaves (fronds) exhibits weak to very strong antioxidant activities (IC50 37.13-225.19 µg/mL), whilst hairs and young fronds showed weak activities, i.e. IC50 179.50-255.49 µg/mL and IC50 544.27->2000 µg/mL, respectively. Hexane fraction from fronds was active against E. coli and S. aureus (43.92% and 46.8%), and from hairs against E. coli (48.1%) in concentration of 250 µg/mL. Gas Chromatography-Mass Spectrometry (GC-MS) analysis indicated that active compounds from fronds extract were dominated by 2H-tetrazole, 5-(thiophen-2yl) methyl (14,29 %), 2-thiophene acetic acid, 2-methyl phenyl ester (14,54%), and phenol, 2,6-bis(1,1-dimethyl ethyl)-4-methyl (10.54%). This study concluded that mature leaves (fronds) of C. contaminans is the potential to be used as antioxidant and antibacterial agents.